Geochemistry, tectonic setting, and petrogenesis of the Coldbrook Group and associated plutons, southern New Brunswick, Canada: A unique Late Ediacaran magmatic episode in Avalonia - Escribano, Alicia P.; Barr, Sandra M. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2023)
The Coldbrook Group is a unique suite of late Ediacaran volcanic and epiclastic rocks deposited in an extensional setting in the Avalonian Caledonia terrane of southern New Brunswick. It is informally divided into a lower part composed of mainly andesitic to dacitic tuffs and epiclastic sedimentary rocks intruded by bimodal plutons, and an upper part composed mainly of mafic flows and tuffs interlayered with but mainly overlain by rhyolitic flows and tuffs and minor epiclastic sedimentary rocks. Recent U–Pb (zircon) dating of four formations in the Coldbrook Group and a subvolcanic granitic dome led to the proposal that the lower and most of the upper Coldbrook Group and associated plutons were formed within <760 kyr at about 551.5 Ma whereas the uppermost rhyolite (Fundy Trail Parkway rhyolite) and underlying basalt of the Hosford Brook Formation formed in a younger event at about 549.5 Ma. Overlapping dates and chemical data also suggest that the subvolcanic granitic domes are the plutonic counterparts of the ca. 551.5 Ma felsic volcanic rocks whereas the other granitic plutons represent extracted melts that evolved separately. Whole-rock geochemical and isotopic data combined with previous field work and map information and integrated with the geochronological data provide new insights into the genesis of these magmas and their change from intermediate to bimodal magmatism. The data indicate that the volcanic and plutonic rocks are mainly tholeiitic and were derived from varying proportions of juvenile melts and recycled older arc lithosphere. The mafic rocks have chemical similarities to flood basalts which inherited some calc-alkalic signatures from older arc-like rocks. Intermediate magmas that formed much of the lower Coldbrook Group had larger lithospheric inputs and thus have mainly calc-alkalic signatures. The Vernon Mountain, Blackall Lake and Silver Hill area rhyolites represent evolved melts derived from the lower Coldbrook Group magmas, and their chemical differences are interpreted to result from melt extraction and solid-liquid dripping magmatic processes. Enhanced extension and thinning led to formation of less lithosphere-contaminated melts that formed the ca. 549.5 Ma bimodal units of the upper Coldbrook Group.